Monoclonal Antibodies: Leading Actors in the Relapsed/Refractory Multiple Myeloma Treatment - Sonia Morè; Maria Teresa Petrucci; Laura Corvatta; Francesca Fazio; Massimo Offidani; Attilio Olivieri (MDPI AG, 2020)
Multiple myeloma is a complex hematologic malignancy, and despite a survival improvement related to the growing number of available therapeutic options since 2000s, it remains an incurable disease with most patients experiencing relapse. However, therapeutic options for this disease are constantly evolving and immunotherapy is becoming the mainstay of the therapeutic armamentarium of Multiple Myeloma (MM), starting with monoclonal antibodies (MoAbs) as elotuzumab, daratumumab and isatuximab. Elotuzumab, the first in class targeting SLAMF7, in combination with lenalidomide and dexamethasone and daratumumab, directed against CD38, in combination with Rd and with bortezomib and dexamethasone (Vd), have been approved for the treatment of relapsed/refractory MM (RRMM) after they demonstrated excellent efficacy. More recently, another anti-CD38 MoAb named isatuximab was approved by FDA in combination with pomalidomide-dexamethasone (Pd) in the same setting. Many phase II and III trials with regimens containing these MoAbs are ongoing, and when available, preliminary data are very encouraging. In this review we will describe the results of major clinical studies that have been conducted with elotuzumab, daratumumab and isatuximab in RRMM, focusing on phase III trials. Moreover, we will summarized the emerging MoAbs-based combinations in the RRMM landscape.